Effects of Zingiber officinale Powder on Semen Characteristic and Blood Serum Sex Hormones Concentration in Broilers Breeder Male - Shanoon , A.K. (International Journal of Poultry Science, 2011)
This study was conducted to examine the effects of Zingiber officinale (ginger) powder on male broiler reproductive system. Zingiber officinale was administered in the feed of two groups of male broiler breeder (30 wk age) at levels of 5 and 10 kg/ton, Third group was a control group (no additive). Treatments were ejaculate volume, sperm concentration, counts, movements, motility and abnormality, blood serum LH, FSH and testosterone concentration. The ginger caused a significant increase (p